1985
DOI: 10.1210/jcem-61-5-976
|View full text |Cite
|
Sign up to set email alerts
|

Elevated ²-Human Chorionic Gonadotropin and Testosterone in Cord Serum of Male Infants of Diabetic Mothers*

Abstract: Leydig cell hyperplasia is a common histological finding in male infants of diabetic mothers. The functional correlates of this histological finding were investigated by measuring beta hCG, testosterone, androstenedione, dihydrotestosterone, and progesterone in mixed cord serum of male and female infants of diabetic mothers (n = 40) and normal mothers (n = 40) at term. Male and female infants of diabetic mothers had significantly higher cord serum beta hCG levels than male and female controls. Male infants of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

1993
1993
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 25 publications
1
6
0
Order By: Relevance
“…true baseline fetal serum hCG concentrations. Our findings confirm that small but significant amounts of serum hCG are present in fetal blood (above 50 IU/I in 13 out of 44 cases), as previously suggested by neonatal cord blood studies (Furuhashi et al, 1982;Barbieri et al, 1985). Therefore, the detection of hCG in an aspirated blood sample is not evidence per se of maternal contamination.…”
Section: Discussionsupporting
confidence: 91%
“…true baseline fetal serum hCG concentrations. Our findings confirm that small but significant amounts of serum hCG are present in fetal blood (above 50 IU/I in 13 out of 44 cases), as previously suggested by neonatal cord blood studies (Furuhashi et al, 1982;Barbieri et al, 1985). Therefore, the detection of hCG in an aspirated blood sample is not evidence per se of maternal contamination.…”
Section: Discussionsupporting
confidence: 91%
“…After birth the infants have less glucose substrate and high levels of insu lin, which result in hypoglycemia. Barbieri et al [8] have reported a positive correlation between cord hCG and tes tosterone levels. These authors found that male infants of diabetic mothers have significantly higher cord serum tes tosterone levels than male controls, female controls, and female infants of diabetic mothers.…”
Section: Discussionmentioning
confidence: 94%
“…A possible explanation for the higher incidence of hypoglycemia in male infants is the effect of higher levels of hCG present in fetuses of diabetic mothers when com pared to fetuses of nondiabetic mothers [8], This may be the result of larger placentas in diabetic pregnancies. High levels of hCG in male fetuses are believed to cause Leydig cell hyperplasia, which results in increased testosterone concentrations [8,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels are elevated in primigravid patients with proteinuric preeclampsia (Said et al, 1984). Amniotic fluid and cord blood levels of hCG are elevated in diabetic mothers (Barbieri et al, 1985(Barbieri et al, , 1986.…”
Section: Fetal Congenital Abnormalitymentioning
confidence: 99%